2013
DOI: 10.1186/1471-230x-13-101
|View full text |Cite
|
Sign up to set email alerts
|

Role of life events in the presence of colon polyps among African Americans

Abstract: BackgroundAfrican Americans have disproportionately higher incidence and death rates of colorectal cancer among all ethnic groups in the United States. Several lifestyle factors (e.g. diet, physical activity and alcohol intake) have been suggested as risk factors for colorectal cancer. Stressful life events have also been identified as risk factors for colorectal cancer. The association between stressful life events and colon polyps, which are precursors of colorectal cancer, has yet to be determined.We aimed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Patients who had previously colonoscopies with polyps removed and admitted for follow-up were so-called “follow-up colonoscopies”. Patients undergoing colonoscopies for symptoms such as abdominal pain or rectal bleeding were defined as “diagnostic colonoscopies” [30].…”
Section: Methodsmentioning
confidence: 99%
“…Patients who had previously colonoscopies with polyps removed and admitted for follow-up were so-called “follow-up colonoscopies”. Patients undergoing colonoscopies for symptoms such as abdominal pain or rectal bleeding were defined as “diagnostic colonoscopies” [30].…”
Section: Methodsmentioning
confidence: 99%
“…A study highlighted the association of total stressful life events and colon polyps in African Americans, supporting the evidence that stress hormones alter the rate of cell growth and proliferation [45]. A study based on a multiethnic colorectal screening [46] observed that individuals with an active lifestyle showed a significantly lower prevalence of adenoma risk, compared to counterparts who had reduced physical activity and demonstrated the development of adenomas in distal colon prevalently.…”
Section: Modifiable Factorsmentioning
confidence: 90%